Integration of Religious Value Education in Theoretical Social Recontruction Curriculum Model - Ali Mahmudi; Mukniah Mukniah; Noor Rofiq (GHAITSA : Islamic Education Journal, 2020)
: This study aims to describe the conception of religious education that emphasizes more students to get debriefing in dealing with life's problems in society, with an integrative approach. Curriculum development is in line with meeting the needs of the problems that are happening. The social reconstruction curriculum model is a development model based on rebuilding people's lives for the better. Religion has a very decisive role in shaping and fostering human life in society to be better, because religion has values ​​and norms that are the source of life guidelines. The research method used by the writer is literature study method. The results of this study are integrated social reconstruction curriculum models and religious education that results.